PERAN LEMBAGA FILANTROPI ISLAM DALAM MENUMBUHKAN EMPATI VOLUNTEER KEPADA ANAK YATIM DHUAFA (Studi Kasus pada Program Temu Pelajar Nusantara di LMI (Lembaga Manajemen Infaq) Malang - Alfiah Ekariani; Ahmad Subekti; Moh. Muslim (VICRATINA, 2020)
Nowdays, in an era that is all digital and can do all things without having to interact direcly, it makes many people neglect that they are social beings and will need each other and will forget that in increasingly widespread with the fading of that understanding. Individualism not only attack public worker but also infects social volunteers. So that in this study aims to determine the role of an Islamic philanthropic institution (Lembaga Manajemen Infaq Malang) in growing empathy for volunteers, especially to vulnerable groups (orphans). This study uses a qualitative approach using interview, documentation, and observation data collection techniques. The result showed that the Islamic philanthropic institute (Lembaga Manajemen Infaq Malang) played a role in fostering empathy for volunteers by conceptualizing various social activities involving several volunteers from various backgrounds. In previous studies many have discussed this, but have not seen it from the point of view of Islam and matching social theories with Islamic theories. The findings in this study will look at phenomena that occur from a social and Islamic perspective. So the result will be able to complement previous research.